Mechanical Chest Compression Devices - A Narrative Review - Kołodziej, Przemysław; Bilyk, Andrii; Król, Maria; Bruska, Natalia Marta; Szplit, Ewa; Więckowska, Katarzyna; Hebda, Patryk; Kubicki, Mateusz; Patalong, Mikołaj; Michnowska, Wiktoria (Journal of Education, Health and Sport, 2026)
Introduction & Aim: Sudden cardiac arrest remains a leading cause of mortality, with global survival rates remaining low. High-quality CPR characterized by adequate depth and minimal interruptions, is the cornerstone of survival. Manual CPR quality often declines due to rescuer fatigue and challenging environments. Mechanical chest compression devices (MCCDs) offer a potential solution to ensure consistent quality. This study aims to provide an overview of MCCDs available in the Polish Emergency Medical System, highlighting their advantages, limitations and applications, while evaluating their clinical effectiveness compared to manual CPR. Material and methods: The study consisted of a descriptive and comparative literature review, focusing on the technical data and clinical evidence (up to 2025) for the AutoPulse, LUCAS, and Corpuls CPR systems used in Poland. Data analysis included RCTS, cohort studies, systematic reviews, and meta-analyses evaluating MCCDs, utilizing PubMed, Scopus, and Google Scholar. Results: MCCDs ensure high-quality, uninterrupted compressions, particularly in challenging transport or specific scenarios, freeing up personnel for other tasks. Large-scale randomized controlled trials (RCTs) and recent meta-analyses demonstrate that MCCDs provide comparable survival outcomes to high-quality manual CPR, with survival rates ranging from 6.0% to 9.4%. However, MCCDs show a significant advantage in specialized scenarios - prolonged transport, catheterization labs, or as a bridge to advanced therapies like eCPR and extracorporeal life support. Conclusions: MCCDs are reliable alternatives for specific clinical situations. Although they involve higher costs and different injury patterns, the benefits of maintaining consistent CPR quality in conditions where manual compressions fail are measurable. Current guidelines recommend their use as a viable alternative in specific, difficult circumstances, rather than as a routine replacement for manual CPR.